Effect of 17‐allylamino‐17‐demethoxygeldanamycin (17‐AAG) on Akt protein expression is more effective in head and neck cancer cell lineages that retain PTEN protein expression. (30th January 2018) - Pontes, Flávia Sirotheau C.; Pontes, Hélder A. R.; de Souza, Lucas L.; de Jesus, Adriana S.; Joaquim, Andrea M. C.; Miyahara, Ligia A. N.; Fonseca, Felipe P.; Pinto Junior, Décio S.
Abstract : Objectives: The aim of this study was to evaluate the expression of Akt, PTEN, Mdm2 and p53 proteins in three different head and neck squamous cell carcinoma (HNSCC) cell lines (HN6, HN19 and HN30), all of them treated with epidermal growth factor (EGF) and 17‐allylamino‐17‐demethoxygeldanamycin (17‐AAG), an inhibitor of Hsp90 protein. Material and Methods: Immunofluorescence and western blot were performed in order to analyze the location and quantification, respectively, of proteins under the action 17‐AAG and EGF. Results: Treatment with EGF resulted in increased levels of Akt, PTEN and p53 in all cell lineages. The expression of Mdm2 was constant in HN30 and HN6 lineages, while in HN19 showed slightly decreased expression. Under the action 17‐AAG, in HN6 and HN19, the expression of PTEN and p53 proteins was suppressed, while Akt and Mdm2 expression was reduced. Finally, in the HN30 cell lineage were absolute absence of expression of Akt, Mdm2 and p53 and decreased expression of PTEN. Conclusion: These data allow us to speculate on the particular utility of 17‐AAG for HNSCC treatment through the inhibition of Akt protein expression, especially in the cases that retain the expression of PTEN protein.